Pan genome and CRISPR analyses of the bacterial fish pathogen Moritella viscosa - Karlsen, Christian; Hjerde, Erik; Klemetsen, Terje; Willassen, Nils Peder (BMC Genomics, 2017)
Source at http://dx.doi.org/10.1186/s12864-017-3693-7 Background: Winter-ulcer Moritella viscosa infections continue to be a significant burden in Atlantic salmon (Salmo salar L.) farming. M. viscosa comprises two main clusters that differ in genetic variation and phenotypes including virulence. Horizontal gene transfer through acquisition and loss of mobile genetic elements (MGEs) is a major driving force of bacterial diversification. To gain insight into genomic traits that could affect sublineage evolution within this bacterium we examined the genome sequences of twelve M. viscosa strains. Matches between M. viscosa clustered, regularly interspaced, short palindromic, repeats and associated cas genes (CRISPR-Cas) were analysed to correlate CRISPR-Cas with adaptive immunity against MGEs. Results: The comparative genomic analysis of M. viscosa isolates from across the North Atlantic region and from different fish species support delineation of M. viscosa into four phylogenetic lineages. The results showed that M. viscosa carries two distinct variants of the CRISPR-Cas subtype I-F systems and that CRISPR features follow the phylogenetic lineages. A subset of the spacer content match prophage and plasmid genes dispersed among the M. viscosa strains. Further analysis revealed that prophage and plasmid-like element distribution were reflected in the content of the CRISPR-spacer profiles. Conclusions: Our data suggests that CRISPR-Cas mediated interactions with MGEs impact genome properties among M. viscosa, and that patterns in spacer and MGE distributions are linked to strain relationships.